2015
DOI: 10.1590/0001-3765201520140098
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Archaeal Communities Variability Associated with Upwelling and Anthropogenic Pressures in the Protection Area of Arraial do Cabo (Cabo Frio region - RJ)

Abstract: Upwelling systems contain a high diversity of pelagic microorganisms and their composition and activity are defined by factors like temperature and nutrient concentration. Denaturing gradient gel electrophoresis (DGGE) technique was used to verify the spatial and temporal genetic variability of Bacteria and Archaea in two stations of the Arraial do Cabo coastal region, one under upwelling pressure and another under anthropogenic pressure. In addition, biotic and abiotic variables were measured in surface and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In the studied region, upwelling events are seasonal and Sargassum growth occurs as a function of its intensity [14]. Thus, upwelling should be considered an important factor causing turnover in community composition of the benthic environment but also of planktonic prokaryotes [4] and eukaryotes [34] which are able to colonize the surface of macroalgal blades [5]. It is expected that Sargassum also selects its biofilm composition since Sargassum produces compounds with antioxidant, antibacterial, antitumoral, antimalarial, antiherbivory and antifouling properties [e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In the studied region, upwelling events are seasonal and Sargassum growth occurs as a function of its intensity [14]. Thus, upwelling should be considered an important factor causing turnover in community composition of the benthic environment but also of planktonic prokaryotes [4] and eukaryotes [34] which are able to colonize the surface of macroalgal blades [5]. It is expected that Sargassum also selects its biofilm composition since Sargassum produces compounds with antioxidant, antibacterial, antitumoral, antimalarial, antiherbivory and antifouling properties [e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In another work, by using DGGE, the same research group found that the archaeal communities were more homogeneous than the bacterial ones in water samples of sites with different degrees of upwelling and downwelling, as well as anthropogenic activities. The archaeal DNA sequences found were clustered in two groups: one associated with coastal waters archaea, and the other with open-sea archaeal DNA [26]. Taken together, the results obtained in these coastal waters studies revealed no significant differences in the archaeal communities of natural and polluted areas.…”
Section: Archaea In Aquatic Environmentsmentioning
confidence: 94%
“…Costa do Sol is considered a phytogeographical enclave (Ab'Saber, 2003) due to the presence of xeric formations such as dry forest and xeric shrubland with Cactaceae (also called "caatinga") (Araujo, 1997). Marine areas close to the municipalities of Armação dos Búzios and Arraial do Cabo are influenced by upwelling, whereby cold waters from the deepest layers emerge to displace surface waters, bringing a large amount of nutrients to enable high primary productivity, which is essential for several economically important marine species (Coelho-Souza et al, 2015). This phenomenon leads to a local decrease in precipitation and, consequently, to the establishment of a dry microclimate, with an average annual precipitation of 850 mm (Barbiere, 1984).…”
Section: Costa Do Solmentioning
confidence: 99%